The Art of silence pantomime with Marcel Marceau [Group IV] - Marceau, Marcel (Chicago Encyclopedia Pritannica Educational Corp., 1975)
Features Marcel Marceau in a performance of pantomime.
The Dream -- The Maskmaker -- Youth maturity, old age and death -- The Side show.
Keywords: Marceau, Marcel; Pantomimes